Learn Adobe Animate CC for multiplatform animations : Adobe Certified Associate Exam Preparation - Labrecque, Joseph; Schwartz, Rob, 1969- (Adobe Press, 2018)
"This study guide uses video integrated with text to help you gain real world skills that will get you started in your career designing and building multiplatform animations using Adobe Animate CC and lays the foundation for taking the Adobe Certified Associate certification exam in that field. A mix of 7 project-based lessons, 10 hours of practical videos, and interactive quizzes prepares you for an entry-level position in a competitive job market.